Оппозитивная модель синонимико–антонимического комплекса со значением «пропорциональность» в языковой картине русского этноса [Articol] - Сирота, Елена (USARB, 2025)
In contemporary research, one of the key topics is the description of the language system and its multilevel organization. A leading trend has become the multifaceted description of lexical phenomena from the perspectives of paradigmatics and syntagmatics. The subject of this study is the interaction of lexical micro-paradigms within a semantic macro-paradigm – an antonymic or synonymous block with the semantics of "proportionality" – and the role of its components in the linguistic worldview of the Russian ethnos. The study identifies and characterizes, according to the lexicographic interpretation model developed by L.G. Babenko, synonymous-antonymous micro-complexes consisting of individual micro-oppositions within the aforementioned synonymous-antonymous block. These micro-complexes reflect patterns of categorizing specific domains of the worldview in national consciousness. As a result, it is concluded that antonymically opposed synonymous series integrate into synonymous-antonymous micro-complexes, underscoring the importance of certain cognitive features in a specific domain that reflect the conceptualization of referents with this meaning.
Keywords: synonymous-antonymous micro-complex; antonym; synonym; lexical paradigm; opposition